Responses of rhizosphere soil properties, enzyme activities and microbial diversity to intercropping patterns on the Loess Plateau of China - Gong, Xiangwei; Liu, Chunjuan; Li, Jing; Luo, Yan; Yang, Qinghua; Zhang, Weili; Yang, Pu; Feng, Baili (Soil & tillage research, 2019)
•Intercropping increased the soil nutrients and enzyme activities of proso millet.•The effect of intercropping on the soil bacterial diversity was larger than fungi.•Intercropping decreased the dominant bacterial abundance of Actinobacteria.•Intercropping did not markedly change the fungal community compositions.•The soil temperature and bulk density contribute more to the bacterial community. Cereal-legume intercropping has been widely used to increase productivity and achieve sustainable development in modern agricultural systems. However, there has been few studies of intercropping in minor grain crops, and we therefore designed an experiment to monitor rhizosphere soil properties, enzyme activities, and the microbial community diversity of proso millet (Panicum miliaceum L.) under proso millet /mung bean intercropping systems on the Loess Plateau of China, and a sole planting was used as a control. Illumina sequencing of the 16S rRNA gene and ITS gene was used to analyze soil microbial (bacterial and fungal) diversity and composition. The results showed that the rhizosphere soil nutrient contents and enzyme activities were higher under intercropping patterns with significant correlations being observed. The physical properties were also changed, including the soil water content, bulk density, and soil temperature. The effect of intercropping patterns on bacterial diversity was larger than that on fungal diversity, especially alpha diversity, although both groups were markedly affected by intercropping patterns. Actinobacteria was the most abundant bacterial phylum, which was decreased by 32.37% under intercropping. Other phylum species, including Proteobacteria, Chloroflexi, Gemmatimonadetes, Acidobacteria, Nitrospirae, and Firmicutes were also markedly affected by intercropping patterns. For the dominant fungal phyla, Ascomycota, Mortierellomycota, and Basidiomycota did not respond substantially to intercropping patterns. Binding spatial ordination analysis demonstrated that soil temperature and bulk density for bacteria and total nitrogen and nitrate contents for fungi contribute more to the microbial community than the other investigated soil parameters, whereas the soil enzyme activities played the same roles in bacteria and fungi. Overall, these results suggest that intercropping alters soil microbial community composition, and the soil bacteria reflect changes in soil properties and enzyme activities better than fungi. Meanwhile, these findings also provide insights into the mechanisms underlying the maintenance of biodiversity in the agro-ecosystems functioning.